Microstructure and radiation shielding capabilities of Al-Cu and Al-Mn alloys - Moamen G. El-Samrah; Islam M. Nabil; Mohamed E. Shamekh; M. Elmasry; M. Osman (Scientific Reports)
Abstract In this study, the microstructure and elemental analysis of aluminum-copper alloy type-2024, Al-2024, and aluminum-manganese alloy type-3003, Al-3003, have been investigated by using a scanning electron microscope (SEM) equipped with Energy dispersive spectroscopy (EDS) detector. Experimental and theoretical radiation shielding studies were performed to assess the radiation shielding capabilities of the studied alloys. Considering the radiation shielding theoretical assessment, some reliable software tools were used, such as Phy-X/PSD, MCNP5, NXCom, and MRCsC. The microstructural observations and results have shown the presence of second phases rich with the main alloying elements in both alloys. Considering Al-2024 alloy, coarse second-phase particles, having a size range of 8–15 μm, were found aligning in lines parallel to the rolling direction, whereas smaller ones, having a size range of 2–8 μm, were found decorated the grain boundaries. Also, dark holes represent the pull-out large particles separated during preparation indicated poor adhesion with the main matrix that could be a result of losing particle coherency with the matrix where the misorientation in-between the atomic planes increase. However, better adhesion of the second-phase particles with the matrix, which were found possessing smaller particle size, have been observed in the Al-3003 alloy indicating good coherency and better manufacturing process for the non-heat-treatable alloy. The second-phase particles in case of Al-2024 alloy were found containing significant content of high-Z elements like Cu with greater volume fraction equals 7.5%. On the other side, Al-3003 alloy has possessed second-phase particles which lack of high-Z elements with only volume fraction equals 3.5%. All the former besides the higher density and content of high-Z elements like copper in Al-2024 alloy in compare to Al-3003 alloy and pure aluminum, led to relatively better radiation shielding capabilities against energetic photons, the highest in the low energy band and decreases with the increase of the photon energy, and slight superiority in the case of fast neutrons with only 3%inc. over pure aluminum. For instance, the radiation protection efficiency (RPE) values dropped from about; 23.2, 21.6, and 20.8% at 0.100 MeV to only 5.7, 5.9, and 5.6% at Eγ = 2 MeV, for; Al-2024, Al-3003, and Al-Pure, respectively."Please check and confirm that the authors and their respective affiliations have been correctly identified and amend if necessary.""confirmed"